A revision of the genus Ima Tindale (Mantodea: Nanomantidae: Fulciniinae) with the description of a new genus - Connors, Matthew G.; Yeeles, Peter; Lach, Lori; Rentz, David C.f. (Zootaxa, 2023)
Ima fusca is one of a number of unusual and infrequently collected Australian mantises about which relatively little is known. Long considered a single species, morphological studies instead revealed the presence of a second cryptic species. We here describe this species as Ima corymbia sp. nov. and redescribe both Ima and Ima fusca in detail. Additionally, we describe a unique, robust species allied to Ima that was discovered with the aid of citizen science, Inimia nat gen. et sp. nov. In light of this discovery, we provide keys to both the Australian Fulciniini genera and to the species of Ima. Finally, we provide detailed behavioural and ecological records for all three species, including the peculiar host plant specificity of Ima spp. We document and discuss this specificity in depth and suggest several possible reasons for its occurrence.